An Algebra for Pattern Matching, Time-aware Aggregates and Partitions on Relational Data Streams - Herbst, Sebastian; Pollner, Thomas Niko; Tenschert, Johannes; Lauterwald, Frank; Endler, Gregor; Meyer-Wegener, Klaus (DEBS '15 Proceedings of the 9th ACM International Conference on Distributed Event-Based Systems, 2015)
Keywords: animal tracking; complex event processing; continuous queries; data stream processing; disjoint union; object tracking; pattern matching; stream algebra; stream partitioning; time-aware aggregates

An Overlay Network for Integration of WSNs in Federated Stream-Processing Environments - Pollner, Thomas Niko; Daum, Michael; Dressler, Falko; Meyer-Wegener, Klaus (The 10th IFIP Annual Mediterranean Ad Hoc Networking Workshop, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4._anove
Keywords: DSAM; Data Stream Application Manager; RDSP; overlay network; WSN; wireless sensor networks; embedded systems; heterogeneous systems; data stream processing; data stream systems; heterogeneous networks; routing; distributed systems; ressource efficiency

Bestimmung der semantischen Eigenschaften von Datenstromsystemen durch Black-Box-Tests - Lauterwald, Frank; Pollner, Thomas Niko; Meyer-Wegener, Klaus (Datenbanksysteme für Business, Technologie und Web (BTW) 2013 - Workshopband, 2013)
Die Semantik von Datenstromsystemen (DSS) ist bislang nicht standardisiert. Für Anwendungsentwickler ist es jedoch wichtig zu wissen, wie sich ein bestimmtes System in einer bestimmten Situation verhält. Ebenso bedeutsam ist das Verhalten für föderierte Datenstromsysteme, die Anfragen automatisch auf verschiedene DSS verteilen. Als Hilfsmittel zur Beschreibung können semantische Modelle dienen. Diese werden parametrisiert und können durch verschiedene Parameterwerte das Verhalten verschiedener Systeme nachbilden. Da bisher auch kein allgemein anerkanntes Modell zur Beschreibung von DSS existiert, muss man sich möglicherweise mit verschiedenen Modellen auseinandersetzen. Daher wäre es hilfreich, die Bestimmung der jeweiligen Parameterwerte weitgehend zu automatisieren, wozu dieser Beitrag eine geeignete Evaluationsumgebung vorstellt. Diese vergleicht die Ausgaben eines DSS mit allen Vorhersagen, die ein Modell für verschiedene Parameter machen kann. Stimmen die Ergebnisse überein, sind die Parameter gefunden. Erfahrungen damit und Beschränkungen dieses Ansatzes werden diskutiert.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD6.bestim
Keywords: data stream systems; semantic model; black box test; simulation; window semantics; DSAM; Data Stream Application Manager

Black-box Determination of Cost Models' Parameters for Federated Stream-Processing Systems - Daum, Michael; Lauterwald, Frank; Baumgärtel, Philipp; Pollner, Thomas Niko; Meyer-Wegener, Klaus (Proceedings of the 15th Symposium on International Database Engineering & Applications, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD6.blackb
Keywords: optimization techniques; heterogeneous event-based systems; data stream systems; performance modeling; cost models; calibration; black-box parameter Determination; DSAM

Demo: Data Stream Application Manager (DSAM) - Lauterwald, Frank; Pollner, Thomas Niko; Daum, Michael; Meyer-Wegener, Klaus (Proceedings of the 6th ACM International Conference on Distributed Event-Based Systems, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD6.procee
Keywords: data stream processing management; federated event-based systems; heterogeneous systems; distributed data stream systems; heterogeneous systems; operator distribution; DSAM; Data Stream Application Manager

Efficient and Cost-aware Operator Placement in Heterogeneous Stream-Processing Environments - Daum, Michael; Lauterwald, Frank; Baumgärtel, Philipp; Pollner, Thomas Niko; Meyer-Wegener, Klaus (Proceedings of the 5th ACM International Conference on Distributed Event-Based Systems, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD6.effici
Keywords: DSAM; Data Stream Application Manager; linear programming relaxation; iterative deterministic rounding; task assignment problem; operator placement; distributed data stream processing

Metadata and Query Management for Distributed Stream Processing in Heterogeneous Sensor Networks - Pollner, Thomas Niko; Meyer-Wegener, Klaus (PhD Workshop @ DEBS 2011, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD6.metada
Keywords: DSAM; Data Stream Application Manager; Data Stream Processing Management; Wireless Sensor Networks; WSN; Metadata Acquisition; Decentralization; Distributed Systems; Ressource Efficiency; Heterogeneous Systems; Query Optimization

Operator Fission for Load Balancing in Distributed Heterogeneous Data Stream Processing Systems - Pollner, Thomas Niko; Steudtner, Christian Thomas; Meyer-Wegener, Klaus (DEBS '15 Proceedings of the 9th ACM International Conference on Distributed Event-Based Systems, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.IMMD.IMMD6.operat
Keywords: algorithms; data stream processing; distributed systems; heuristics; operator fission; operator placement; DSAM

Placement-Safe Operator-Graph Changes in Distributed Heterogeneous Data Stream Systems - Pollner, Thomas Niko; Steudtner, Christian Thomas; Meyer-Wegener, Klaus (Datenbank-Spektrum, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.IMMD.IMMD6.placem_9
Keywords: Data stream systems; Query optimization; Operator placement; Distributed data stream processing; Heterogeneous systems; DSAM

Placement-Safe Operator-Graph Changes in Distributed Heterogeneous Data Stream Systems - Pollner, Thomas Niko; Steudtner, Christian Thomas; Meyer-Wegener, Klaus (Datenbanksysteme für Business, Technologie und Web (BTW 2015) - Workshopband, 2015)
Data stream processing systems enable querying continuous data without first storing it. Data stream queries may combine data from distributed data sources like different sensors in an environmental sensing application. This suggests distributed query processing. Thus the amount of transferred data can be reduced and more processing resources are available. However, distributed query processing on probably heterogeneous platforms complicates query optimization. This article investigates query optimization through operator graph changes and its interaction with operator placement on heterogeneous distributed systems. Pre-distribution operator graph changes may prevent certain operator placements. Thereby the resource consumption of the query execution may unexpectedly increase. Based on the operator placement problem modeled as a task assignment problem (TAP), we prove that it is NP-hard to decide in general whether an arbitrary operator graph change may negatively influence the best possible TAP solution. We present conditions for several specific operator graph changes that guarantee to preserve the best possible TAP solution.
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD6.placem
Keywords: data stream systems; query optimization; operator placement; distributed data stream processing; heterogeneous systems; DSAM

Technische Grundlagen für eine laufzeitadaptierbare Transaktionsverwaltung - Irmert, Florian; Neumann, Christoph; Daum, Michael; Pollner, Thomas Niko; Meyer-Wegener, Klaus (Datenbanksysteme in Business, Technologie und Web (BTW), 2009)
Auf spezielle Anwendungen zugeschnitte Datenbankverwaltungssysteme (DBMS) erfordern in den meisten Fällen Individuallösungen, welche einen erhöhten Entwicklungs- und Wartungsaufwand mit sich bringen. Es fehlen modulare DBMS-Architekturen als konfigurierbare Standardlösung, die beliebig schlanke als auch umfangreiche Architekturen ermöglichen. Die Transaktionsverwaltung als querschneidender Belang durchdringt in herkömmlichen DBMS die Architektur und verhindert die Modularisierung. In dieser Arbeit wird die Transaktionsverwaltung aus einem DBMS herausgelöst und durch eine eigenständige, wiederverwendbare Komponente realisiert. Die Architektur der gekapselten und wiederverwendbaren Transaktionsverwaltung wird dokumentiert, sowie die aspektorientierte Verknüpfung zwischen reduziertem DBMS und separater Transaktionsverwaltung beschrieben. Als Grundvoraussetzung für zukünftige, sich selbstverwaltende DBMS kann die Transaktionsverwaltung zur Laufzeit dynamisch hinzugefügt und entfernt werden. Die prototypische Implementierung wird an Hand von SimpleDB in Verbindung mit einem dynamischen AOP Framework erläutert.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.IMMD6.techni
Keywords: data base management systems; transactions; modularization; cross-cutting concerns; dynamic aspect oriented programming; AOP; CoBRA DB

Umgang mit semantischer Heterogenität bei der Integration stromverarbeitender Systeme - Wie erzeugt man die vom Benutzer gewünschten Ergebnisse? - Lauterwald, Frank; Daum, Michael; Pollner, Thomas Niko; Meyer-Wegener, Klaus (Datenbank-Spektrum, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.IMMD.IMMD6.umgang
Keywords: Datenströme; Datenstromsysteme; Verteilung; Semantische Heterogenität; Split-Semantik; Fenstersemantik; Load-Shedding-Semantik; Qualität; Soll-Ist-Vergleich; DSAM; Data Stream Application Manager